Design and validation of a MIMO radar and communication system using 5G-NR waveforms - Silva, Jorge Henrique Gomes (2021)
With the emergence of the large bandwidths provided by the new radio technologies, such as 5G-NR, and the increasingly pronounced trends towards using wireless communication devices, we are starting to see congestion of the spectrum traditionally used for communication purposes. In this dissertation, the design, prototyping, and experimental validation of a MIMO Radar system that uses 5G-NR signals, originally intended for communication purposes, is demonstrated and analysed in detail. Then, the concepts behind the use of OFDM communication signals for radar purposes are analysed, and the advantages of using MIMO radar systems are addressed. Next, the steps necessary to develop a 5G-NR simulator are described in detail, and the simulator is numerically and experimentally validated considering a communication scenario. After that, the use of 5G-NR signals for radar purposes is numerically validated through simulation and experimentally through the design, assembly, and analysis of the radar system. Finally, the design, prototyping, and analysis of a MIMO radar system, using components previously developed by the RETIOT project, is performed, proceeding to an experimental validation using different processing algorithms and comparing directly with the numerically simulated and expected results.